The relationship between leisure activities and mental health disorders among higher education students in Malaysia - Lim Lee Ping; Ong Choon Hee; Tan Owee Kowang; Chi-Hua Wu (Institute of Advanced Engineering and Science, 2024)
This study investigates the association between leisure activities (recreation, sports, social contact, artistic, cultural, religious, and rest) and mental health disorders among Malaysian university students. There were 332 respondents enrolled in the public and private universities, polytechnics and other higher academic institutions in Malaysia were surveyed using a quantitative questionnaire. The study performed multiple regression and correlation analyses on the data using the statistical package for social science (SPSS). The findings indicated that six out of seven categories of leisure activities were significantly linked to mental health issues. The six types of leisure time activities were recreation, sports, social interaction, cultural, religious, and rest. Cultural activities have the highest impact on mental health, with the highest beta value. The universities and polytechnics should consider launching several types of leisure activities and tailor specific activities that may reduce mental health issues.